MGOPT method for semilinear elliptic optimal control problems - Vallejos, Michelle
A numerical technique called multigrid for optimization or MGOPT that solves semilinear elliptic optimal control problems is presented. The given problem is discretized by finite difference technique incorporated with a multigrid strategy. to illustrate the MGOPT method, we focus on minimization problems governed by semilinear elliptic differential equations.
Issued also online.
Keywords: Semilinear elliptic optimal control; Multi-grid scheme; MGOPT method